Music performance anxiety inventory for adolescents: psychometric properties of the Portuguese version - Dias, Pedro (2022)
The aim of the current study was to develop the Portuguese version of the Music Performance Anxiety Inventory for Adolescents (MPAI-A) and to examine its psychometric properties with a sample of 161 adolescent music students in Portugal. Participants completed the Portuguese version of the MPAI-A, the State-Trait Anxiety Inventory for Children, and a sociodemographic questionnaire. The MPAI-A psychometric properties were examined for validity and reliability. A two-factor structure was identified through Exploratory Factor Analysis: F1-Music Performance Anxiety cognitive and somatic symptoms; F2-Performance. Concurrent and known-group validity were established, and reliability scores were appropriate for the dimensions and total score. Results provide initial evidence of the appropriateness of the Portuguese version of the MPAI-A. Practical implications are discussed and future studies with this instrument are suggested.